(untitled) (Research, Society and Development, 2023)
Introduction: The carbon neutral standard, or also known as carbon neutral or “zero net emissions” standard, aims to balance the greenhouse gas emissions released into the atmosphere with the elimination or compensation of the same amount of emissions. In many countries, this standard has been implemented with certain policies and measures to move towards carbon neutrality in different international agreements. Said policies include actions such as the promotion of renewable energies, energy efficiency, use of renewable materials, etc. Objective: to determine the importance of Carbon Neutral model in dental clinics. Materials and Methods: In this article, a review of the literature about the Carbon Neutral Standard and its impact on Companies and Dentistry was carried out, using scientific articles and other research documents from the Scopus, Google Scholar, Scielo databases. and the website of the Ministry of the Environment of Ecuador. Conclusion: The carbon neutral standard promotes environmental awareness and responsibility in companies, reducing emissions, energy and water consumption, and also minimizing the consumption of single-use plastics. Dental offices can be polluting, but the implementation of reusable supplies benefits the environment and saves money. In Ecuador, carbon neutral certifications endorsed by the National Environmental Authority can be obtained.